Analyzing The Cultural Values of Figurative Language Found In Pamona Songs - Gadi, Deane Gloria; Lantu, Ika Paramitha (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
The aim of this study was to identify the themes that conveyed through of figurative language present in Pamona songs and to find out the cultural values. Using a descriptive qualitative method, this study interprets data sourced from four Pamona songs taught in schools. This study explores the use of figurative language in the lyrics of the Pamona song as well as the themes also cultural values conveyed through the figurative language. The themes conveyed are the beauty of nature, love for the homeland, and advice. Then the cultural values found in the songs are togetherness and good manners. The study concludes that Pamona songs are a valuable tool for educators. The figurative language within the songs’ lyrics effectively conveys cultural values and themes, helping to build students’ character and strengthen their local identity while preparing them for a global world. By using these songs in English classes, teachers can promote critical thinking and ensure students maintain their cultural roots.